The Effect of Bladder (BL) 32 Acupressure Point on Reducing Labor Pain Intensity During Active Phase of First Stage in Laboring Women - Sari, Daris Yolanda (CV. Publikasi Indonesia, 2025)
Labor pain is a physiological response experienced by mothers before the birth process. The level of pain felt can vary between mothers and may even differ in the same mother during each labor process. This study aims to determine the effect of Bladder (BL) 32 acupressure point on reducing labor pain intensity during the active phase of the first stage in laboring women in TPMB A area, Purwakarta Regency in 2024. This research used a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest design. The research sample consisted of 32 respondents assessed before and after the intervention. The sampling technique used was purposive sampling. The instrument used to measure pain was the Numeric Rating Scale (NRS). Data analysis was carried out using the Wilcoxon test. The results showed that labor pain intensity before the intervention had a mean of 7.28, while labor pain intensity after the intervention had a mean of 5.41, resulting in a mean reduction of 1.88. The p-value obtained was 0.000 (p<0.05). It can be concluded that there is a significant effect of the BL32 acupressure point on reducing labor pain intensity during the active phase of the first stage in laboring women in TPMB A area, Purwakarta Regency, in 2024. The implication of this research is that midwives should perform BL32 acupressure to reduce pain during labor.